2024
DOI: 10.1039/d3dt02692b
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of N-doped C-encapsulated flower-like nickel-based heterostructured microsphere anodes for high-capacity and stable lithium storage

Zhicheng Yu,
Shahriman Zainal Abidin,
Natrina Mariane P. Toyong
et al.

Abstract: The design and fabrication of flower-like core–shell NiS/Ni3(BO3)2/NC heterostructured microspheres exhibiting superior electrochemical performances in LIBs are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…3f) show the presence of pyridine N (398.2 eV), pyrrolic N (401.8 eV), and graphitic N (404.8 eV). 30,41 It can be found that the pyridine N and pyrrolic N exhibit a high content compared to graphitic N, causing more active sites for polysulfide adsorption due to electron delocalization. 15,42 The XPS characterization results further prove the successful synthesis of the MoO 3 –MoSe 2 –NC composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3f) show the presence of pyridine N (398.2 eV), pyrrolic N (401.8 eV), and graphitic N (404.8 eV). 30,41 It can be found that the pyridine N and pyrrolic N exhibit a high content compared to graphitic N, causing more active sites for polysulfide adsorption due to electron delocalization. 15,42 The XPS characterization results further prove the successful synthesis of the MoO 3 –MoSe 2 –NC composite.…”
Section: Resultsmentioning
confidence: 99%
“…However, the existence of Mo–O bonds is conducive to the adsorption of polysulfide ion intermediates, effectively reducing the loss of active substances. 29,30 Indeed, phase engineering or surface engineering has extensive applications in energy storage and conversion because of their interface effects. Compounding components with distinct band gaps in heterostructures can improve the surface reaction kinetics and enhance the charge transport due to the internal electric field in the interface, thereby leading to significantly improved electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%